Association Between Catalase Gene Polymorphisms and Risk of Chronic Hepatitis B, Hepatitis B Virus-Related Liver Cirrhosis and Hepatocellular Carcinoma in Guangxi Population: A Case–Control Study. Issue 13 (April 2015) - Liu, Yanqiong; Xie, Li; Zhao, Jiangyang; Huang, Xiuli; Song, Liuying; Luo, Jingrong; Ma, Liping; Li, Shan; Qin, Xue
Abstract : Abstract: Reactive oxygen species (ROS) play critical roles in hepatocarcinogenesis. The catalase (CAT) enzyme is involved in the repair of ROS. Therefore, we investigate the association between CAT gene polymorphisms and the risk of hepatocellular carcinoma (HCC). A total of 715 subjects were divided into 4 groups: 111 chronic hepatitis B (CHB) patients, 90 hepatitis B virus (HBV)-related liver cirrhosis (LC) patients, 266 HBV-HCC patients, and 248 healthy controls. The polymerase chain reaction-restriction fragment length polymorphism strategy was used to detect CAT gene rs1001179, rs769217, and rs7943316 polymorphisms. Binary logistic regression analyses adjusting for sex, age, ethnicity, smoking and alcohol consumption, and body mass index suggested that subjects carrying the rs769217 T allele were at marginally increased risk of CHB, LC, and HCC, with adjusted odds ratios (ORs) of 1.51 (95% confidence interval [CI] = 1.04–2.20, P = 0.029), 1.48 (95% CI = 1.03–2.14, P = 0.035), and 1.51 (95% CI = 1.14–1.98, P = 0.004), respectively. Similarly, those individuals carrying the rs769217 TT genotype had a moderately increased risk of CHB, LC, and HCC, with adjusted ORs of 2.11 (95% CI = 1.05–4.22, P = 0.035), 2.00 (95% CI, 1.01–3.95, P = 0.047), and 1.93 (95% CI = 1.14–3.28, P = 0.015), respectively. Moreover, subjects carrying the rs769217 CT genotype and at least 1 copy of the T allele (dominant model) were 1.78 times and 1.83 times more likely to develop HCC, respectively (OR = 1.78, 95% CI = 1.16–2.73, P = 0.009 and OR = 1.83, 95% CI = 1.23–2.71, P = 0.003). This association between CAT rs769217 T alleles and HCC risk is significantly strengthened among men, nonsmokers, nondrinkers, and among individuals <50 years of age. Furthermore, we found 1 high-risk haplotype GTA for CHB (OR = 1.45, 95% CI = 1.05–2.01) and 1 protective haplotype GCA for HCC risk (OR = 0.67, 95% CI = 0.52–0.87). We did not found any significant difference in CAT rs1001179 and rs7943316 polymorphisms between controls and cases. Our findings suggest that the CAT rs769217 T allele is associated with increased risk of CHB, HBV-LC, and HBV-HCC in Guangxi population. Abstract : Supplemental Digital Content is available in the text